Seasonality of Rural Finance - Khandker, Shahidur R.; Samad, Hussain A.; Badruddoza, Syed (World Bank, Washington, DC, 2017)
Simultaneity of borrowing, withdrawal of savings, and loan defaults due to the pronounced seasonality of agriculture often leads to investment failure of rural financial institutions. Lack of borrowing leads to lack of in-come- and consumption-smoothing, and in turn, causes inefficient resource allocation by rural households. Financial institutions that are active in rural areas take different measures to address the covariate risks in intermediation. For example, microfinance institutions have sought various measures such as supporting non-farm activities to diversify income, introducing seasonal loans, and bringing flexibility in loan repayments to reduce non-payments in lean seasons. This paper examines whether the financial inclusion policies of micro-finance institutions have successfully helped reduce the adverse effects of covariate risks. Analysis of house-hold and program level data from Bangladesh suggests that despite the innovative measures taken by the MFIs to cope with the covariate risks, seasonality of income still affects seasonality of borrowing and investment decisions of both the households and MFIs beyond and above what is caused normally by agricultural seasonality. Innovation is needed to promote, among other things, sectoral diversification of financial inter-mediation and to avert the extreme seasonality of rural income. Rural labor markets should be diversified enough to address the seasonality of income and consumption. Public policies guiding rural financial inter-mediation must reflect such realities of rural economies.